2017
DOI: 10.3892/ijmm.2017.3203
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of Valeriana fauriei regulates BDNF signaling in an animal model of fibromyalgia

Abstract: The genus Valeriana has been widely used in popular medicine for centuries, to treat sleep disorders, anxiety, epilepsy and insomnia. Recent studies have focused on the novel pharmacological effects of Valeriana fauriei Briq. (VF) species. Previous studies have attempted to determine the pharmacological functions of Valeriana in various human diseases, particularly with regards to its neuroprotective effects, and its ability to reduce pain and stress. The present study constructed an animal model of fibromyalg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Review of the literature for the intermittent cold-stress model of FMS-like pain in animals identified 4 studies that investigated associated alterations in affect (Table 5). Although the current literature is limited, current data supports the model's ability to induce depression-like behaviors in animals as has been measured in TST [137], the evasion test [138], and FST [139]. However, one study did fail to find significant differences is TST behavior [33].…”
Section: Cold Stress Evaluationsupporting
confidence: 62%
See 1 more Smart Citation
“…Review of the literature for the intermittent cold-stress model of FMS-like pain in animals identified 4 studies that investigated associated alterations in affect (Table 5). Although the current literature is limited, current data supports the model's ability to induce depression-like behaviors in animals as has been measured in TST [137], the evasion test [138], and FST [139]. However, one study did fail to find significant differences is TST behavior [33].…”
Section: Cold Stress Evaluationsupporting
confidence: 62%
“…Within these limited studies, treatments for significantly improving depression-like behaviors in animals produced by the cold stress model have been identified [137][138][139]. Gabapentin was identified as having improved evasion behaviors, implicative of improvement in depression-like behaviors, alongside improvement in evoked pain measures within animals subjected to the cold stress model [138].…”
Section: Cold Stress Evaluationmentioning
confidence: 99%
“…The effects of V. adscendens extracts on the central nervous system have been associated with the interaction with serotoninergic, dopaminergic, and noradrenergic receptors [ 95 ]. On the other hand, studies from Lee et al [ 39 ] suggest that the antinociceptive effects of V. fauriei can be related to modulatory effects on the BDNF signaling pathway in the hippocampus and medial prefrontal cortex. Recently, Choi et al [ 96 ] demonstrated that this species exerts antidepressant effects through its anti-inflammatory and antioxidant effects by inhibiting BDNF expression.…”
Section: Molecular Mechanism Of Action Of Pharmacological Potentialmentioning
confidence: 99%
“…RT-quantitative PcR (RT-qPcR) was performed using the SYBR ® Premix Ex Taq™ II kit (Takara Bio, Inc.) on an Applied Biosystems QuantStudio™ 6 Flex thermocycler (Thermo Fisher Scientific, Inc.), and the relative gene expression was normalized to GAPdH expression, and was calculated using the 2 -ΔΔcq relative quantification method (26). Statistical analysis of each group included three independent samples and the intergroup difference was analyzed via Student's t-test (27).…”
Section: Isolation and Biological Characteristic Evaluation Of A Novel Type Of Cartilage Stem/progenitor Cell Derived From Small-tailed Hmentioning
confidence: 99%